2016
DOI: 10.1016/j.quascirev.2016.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Paleo-environmental gateways in the eastern Canadian arctic – Recent isotope hydrology and diatom oxygen isotopes from Nettilling Lake, Baffin Island, Canada

Abstract: a b s t r a c tNettilling Lake is located on Baffin Island, Nunavut, Canada between the areas of past warming (Canadian High Arctic to the North) and climatic stability (Northern Quebec and Labrador region to the South). Despite being the largest lake in the Nunavut region with a postglacial marine to lacustrine transition history only a few paleo-environmental investigations were completed in this area. O silica-water of 1000 ln a (silica-water) ¼ 40.2‰ for sub-recent diatoms of Nettilling Lake was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 49 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…d 18 O diatom is controlled by several environmental parameters which depend on local hydrology, climate, and the seasonality of diatom growth Rioual et al 2001;Jones et al 2004;Rosqvist et al 2004;Leng and Barker, 2006;Schiff et al 2009;Mackay et al 2011;Meyer et al 2015;Chapligin et al 2016). Previous work by Bailey et al (2015) showed that the surface core d 18 O diatom record from Heart Lake correlates significantly with the winter NPI during the instrumental period (1900e2009 AD) (r ¼ 0.43, p < 0.02, n ¼ 28).…”
Section: Oxygen Isotope Paleohydrology and Paleoclimatologymentioning
confidence: 98%
“…d 18 O diatom is controlled by several environmental parameters which depend on local hydrology, climate, and the seasonality of diatom growth Rioual et al 2001;Jones et al 2004;Rosqvist et al 2004;Leng and Barker, 2006;Schiff et al 2009;Mackay et al 2011;Meyer et al 2015;Chapligin et al 2016). Previous work by Bailey et al (2015) showed that the surface core d 18 O diatom record from Heart Lake correlates significantly with the winter NPI during the instrumental period (1900e2009 AD) (r ¼ 0.43, p < 0.02, n ¼ 28).…”
Section: Oxygen Isotope Paleohydrology and Paleoclimatologymentioning
confidence: 98%
“…Canada (Chapligin et al, 2016). High-resolution isotope analysis combined with the study of the specific composition of diatom assemblages were an important addition to palaeoenvironmental.…”
Section: Extracting Hydroclimatic Information From Arctic Lakesmentioning
confidence: 99%
“…Diatom oxygen isotopes in combination with data of taxonomy analysis have become one of the most reliable sources of information about past ecological, hydrological, environmental and climate changes especially for northern regions where ice archives are unavailable and/ or biogenic carbonates limited Jones et al 2004;Swann et al 2010;Chapligin et al 2012bChapligin et al , 2016Narancic et al 2016). Existing d 18 O diatom records have been interpreted to evaluate past changes in air temperature (Chapligin et al 2012b), precipitation amounts and/or air-mass sources (Barker et al 2001;Shemesh et al 2001;Jones et al 2004;Rosqvist et al 2004;Kostrova et al 2013;Meyer et al 2015;Bailey et al 2018), the precipitation/evaporation balance (Rioual et al 2001;Kostrova et al 2014) and palaeohydrological variability (Mackay et al 2008(Mackay et al , 2011(Mackay et al , 2013Chapligin et al 2016;Narancic et al 2016). Existing d 18 O diatom records have been interpreted to evaluate past changes in air temperature (Chapligin et al 2012b), precipitation amounts and/or air-mass sources (Barker et al 2001;Shemesh et al 2001;Jones et al 2004;Rosqvist et al 2004;Kostrova et al 2013;Meyer et al 2015;Bailey et al 2018), the precipitation/evaporation balance (Rioual et al 2001;Kostrova et al 2014) and palaeohydrological variability (Mackay et al 2008(Mackay et al , 2011(Mackay et al , 2013Chapligin et al 2016;Narancic et al 2016).…”
mentioning
confidence: 99%
“…Diatoms, photosynthetic microalgae with an external frustule composed of biogenic silica (opal, SiO 2 ÁnH 2 O), are abundant in most aquatic systems and typically well preserved in lacustrine sediments (Round et al 1990). Diatom oxygen isotopes in combination with data of taxonomy analysis have become one of the most reliable sources of information about past ecological, hydrological, environmental and climate changes especially for northern regions where ice archives are unavailable and/ or biogenic carbonates limited Jones et al 2004;Swann et al 2010;Chapligin et al 2012bChapligin et al , 2016Narancic et al 2016). Lacustrine d 18 O diatom reflects the oxygen isotope composition of the lake water (d 18 O lake ) and lake temperature (T lake ) (Leng & Barker 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation